2017
DOI: 10.1186/s40168-017-0295-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of the gut microbiome and metabolome in preterm neonates with late onset sepsis and healthy controls

Abstract: BackgroundLate onset sepsis (LOS) in preterm infants is associated with considerable morbidity and mortality. While studies have implicated gut bacteria in the aetiology of the disease, functional analysis and mechanistic insights are generally lacking. We performed temporal bacterial (n = 613) and metabolomic (n = 63) profiling on extensively sampled stool from 7 infants with LOS and 28 matched healthy (no LOS or NEC) controls.ResultsThe bacteria isolated in diagnostic blood culture usually corresponded to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(181 citation statements)
references
References 50 publications
7
157
2
Order By: Relevance
“…In addition to this, a longitudinal study was conducted for a subset of BA infants before and after the Kasai portoenterostomy. 25 Bifidobacterium, one of the dominant strict anaerobes in the gut of healthy infants, 26,27 was significantly decreased in BA patients, which is consistent with a previous study performed on stool culture. In this study, 16S rRNA sequencing data indicated that Firmicutes and Proteobacteria numbers were observed to be higher at the phylum level in BA patients.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to this, a longitudinal study was conducted for a subset of BA infants before and after the Kasai portoenterostomy. 25 Bifidobacterium, one of the dominant strict anaerobes in the gut of healthy infants, 26,27 was significantly decreased in BA patients, which is consistent with a previous study performed on stool culture. In this study, 16S rRNA sequencing data indicated that Firmicutes and Proteobacteria numbers were observed to be higher at the phylum level in BA patients.…”
Section: Discussionsupporting
confidence: 90%
“…Since the causative agent of LOS is often abundantly present in the days preceding disease onset and each bacterial species produces a unique VOC fingerprint, we suggest that fecal VOCs may allow for the preclinical detection of pathogens at the species level [33]. Another recent trial by Stewart et al [63] partly underlines this hypothesis. When preterm infants with LOS were compared to controls by microbiota and metabolomics analysis, no distinct conclusion could be made about the infants with LOS.…”
Section: Microbiota-based Diagnosis Of Necmentioning
confidence: 83%
“…However, cohousing may not be sufficient to completely transfer all properties of the microbiota. For example, the bacterial composition and metabolomics profiles may not be parallel, meaning that different microbial compositions cannot be equated to different metabolomics profiles . Bacterial function may also be influenced by other independent factors, such as the physiological condition of the host intestine, food intake, and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the bacterial composition and metabolomics profiles may not be parallel, meaning that different microbial compositions cannot be equated to different metabolomics profiles. (39) Bacterial function may also be influenced by other independent factors, such as the physiological condition of the host intestine, food intake, and lifestyle. Another contributor to microbial responses is the release of stress factors from the gut into the intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%